2008
DOI: 10.2174/157341308784340804
|View full text |Cite
|
Sign up to set email alerts
|

Mycosynthesis of Silver Nanoparticles Using the Fungus Fusarium acuminatum and its Activity Against Some Human Pathogenic Bacteria

Abstract: We report extracellular mycosynthesis of silver nanoparticles by Fusarium acuminatum Ell. and Ev. (USM-3793) isolated from infected ginger (Zingiber officinale). An aqueous silver nitrate solution was reduced to metallic silver when exposed to F. acuminatum cell extract leading to the appearance of a brown color within 15-20 minutes. The color is due to the formation of silver nanoparticles and the excitation of surface plasmons. The optical spectrum showed the plasmon resonance at 420 nm and analysis by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
235
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(250 citation statements)
references
References 41 publications
15
235
0
Order By: Relevance
“…The biggest advantage of this protocol based on purified enzyme was the development of a new approach for green synthesis of nanomaterials over a range of chemical compositions and shapes without possible aggregation. Ingle et al (Ingle et al 2008) demonstrated the potential ability of Fusarium acuminatum Ell. and Ev.…”
Section: Synthesis Of Silver Nanoparticles By Fungimentioning
confidence: 99%
“…The biggest advantage of this protocol based on purified enzyme was the development of a new approach for green synthesis of nanomaterials over a range of chemical compositions and shapes without possible aggregation. Ingle et al (Ingle et al 2008) demonstrated the potential ability of Fusarium acuminatum Ell. and Ev.…”
Section: Synthesis Of Silver Nanoparticles By Fungimentioning
confidence: 99%
“…Filamentous fungi on the other hand are capable of synthesizing the silver nanoparticles extracellularly but the downstream processing and the biomass handling make them difficult [10][11][12].…”
mentioning
confidence: 99%
“…In fact, a number of different species of bacteria and fungi are able to reduce metal ions producing metallic nanoparticles with antimicrobial properties. Recently, it has been shown that silver nanoparticles produced by the fungus F. acuminatum have efficient antibacterial activity against multidrug resistant and highly pathogenic, Salmonella typhi (109). Additionally, plant extracts can also be used to obtain metallic nanoparticles (110).…”
Section: Metal Nanoparticles As Antisalmonellosis Agentsmentioning
confidence: 99%
“…Silver nanoparticles Salmonella typhi (141) Silver nanoparticles Salmonella typhimurium (142) Silver bionanoparticles Salmonella typhi (143) Silver bionanoparticles Salmonella paratyphi (144) TiO2 nanoparticles Salmonella typhimurium (145) ZnO nanoparticles Salmonella typhimurium (145) Silver nanoparticles Salmonella typhus (146) Iron nanoparticles Salmonella paratyphi (147) silver nanoparticles Not specified (148) Silver Nanoparticles Salmonella typhimurium (149) Silver bionanoparticles Salmonella typhi (150) Ag-SiO2 anoparticles Salmonella typhimurium…”
Section: Metal Nanoparticles As Antisalmonellosis Agentsmentioning
confidence: 99%